Melting thermal transportation in bioconvection Casson nanofluid flow over a nonlinear surface with motile microorganism: Application in bioprocessing thermal engineering - Li, Yijie; Majeed, Aaqib; Ijaz, Nouman; Barghout, Kamal; Ali, Mohamed R.; Muhammad, Taseer (Case studies in thermal engineering, 2023)
Bioconvection in fluids can be significantly influenced by melting thermal transport, especially when it comes to heat transfer and energy transmission. In a fluid, microbes or biological particles may move together due to physical or chemical gradients, such as light, temperature, or chemical concentrations. This process is known as bioconvection. In bioprocessing, mobile microorganisms can be employed to create beneficial substances including biofuels, medicines, and food additives. They can move around freely in the fluid thanks to their motility, which improves the mixing and distribution of other substrates like nutrients. The main outcomes of the current study are to provide the comprehensive numerical analysis of existing situation where the melting transportation impact along with the action of microorganisms on MHD non-Newtonian nano fluid model under velocity, thermal and concentration slip. Also, our derived results are validated with the previously published data against various convergence flow parameters, which are demonstrated through tables. To provide more meaningful data, numerous mathematical and technical constraints are taken into consideration. Using the required conversion technique, the system of PDEs is transmuted into a non-linear ODEs. Using the shooting strategy, evaluate expressions numerically by transforming them with the MATLAB function bvp4c. The literature elaborates on a few observations on the bio-convection process and its additional unique features. The graphs demonstrate the effects of various flows on dimensionless quantities. The current theoretic model might be used to increase heat transmission, engineering practices, and thermal energy.